Applications of Ion Exchange Materials in Chemical and Food Industries - Inamuddin; Rangreez, Tauseef Ahmad; M. Asiri, Abdullah (Springer International Publishing : Imprint: Springer, 2019)
This book presents the applications of ion-exchange materials in the chemical and food industries. It includes topics related to the application of ion exchange chromatography in water softening, purification and separation of chemicals, separation and purification of food products and catalysis. This title is a highly valuable source of knowledge on ion-exchange materials and their applications suitable for postgraduate students and researchers but also to industrial R&D specialists in chemistry, chemical, and biochemical technology. Additionally, this book will provide an in-depth knowledge of ion-exchange column and operations suitable for engineers and industrialists.